Late Silurian vertebrate microfossils from the Carnarvon Basin, Western Australia. Issue 2 (3rd April 2019) - Burrow, Carole J.; Turner, Susan; Trinajstic, Kate; Young, Gavin C.
Abstract : Burrow, C.J., Turner, S., Trinajstic, K. & Young, G.C., 27 February 2019. Late Silurian vertebrate microfossils from the Carnarvon Basin, Western Australia. Alcheringa 43, 204–219. ISSN 0311-5518. A core sample from the offshore Pendock 1A well, Carnarvon Basin, Western Australia yielded microvertebrate residues at an horizon in the lower part of the Hamelin Formation, dated as late Silurian, ? Ludlow, based on associated conodonts. The fish fauna comprises loganelliiform thelodont scales, the ? stem gnathostome Aberrosquama occidens nov. gen. et sp., the acanthodian Nostolepis sp. aff. N. alta, and the ? stem osteichthyan Andreolepis sp. aff. A . petri . Because of the paucity of the material, and some differences between the Pendock scales and those of established species, a precise age can not be confirmed; however, the composition of the fauna at generic level most closely resembles that of late Silurian (Ludlow) assemblages from northern Eurasia. Carole J. Burrow* [ carole.burrow@gmail.com ], Geosciences, Queensland Museum, Hendra QLD 4011, Australia; Susan Turner [ palaeoich@yahoo.com ], Geosciences, Queensland Museum, Hendra QLD 4011, Australia; Kate Trinajstic [ k.trinajstic@curtin.edu.au ], School of Molecular and Life Sciences, Curtin University, Perth, WA 6102, Australia; Gavin C. Young [ gavin.young@anu.edu.au ], Research School of Physics and Engineering, Australian National University, Canberra, ACT 2000, Australia.